KREATIVITAS MAHASISWA S1 TATA BUSANA DALAM MATA KULIAH DESAIN RAGAM HIAS JURUSAN KESEJAHTERAAN KELUARGA - Sabri, Bismeri; Katin, Yusmar Emmy; Idrus, Yenni (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2012)
The problem in this study is characterized by decorative generated monotonous, rigid and difficult to find new ideas. The research objective was to express creativity S1 students in the subject of fashion design decorative Department of Family Welfare. Type of research is descriptive quantitative research population Family Welfare S1 students of fashion. Samples were taken with a total sampling technique. The data was collected using a Likert scale questionnaire. For the reliability of the instrument used Cronbach alpha formula. For the presentation of data analysis techniques used. The results seen from the six indicators are: 1. Openness to new experiences, considered good enough 2. Flexibility in thinking, considered good enough 3. Freedom of expression considered quite good 4. It has a pretty good fantasy categorized 5. The interest in creative activities categorized quite well 6. Confidence in their own ideas considered good enough. Based on the distribution of scores in a variable decorative creativity Creativity Students are classified as being categorized, while the level of achievement of the results of questionnaires in the category quite well. Can be seen and verified from the collection of student assignment in the form of a portfolio.